Methodological Basis of KPI Motivation; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 26 : Responsible Research and Innovation (RRI 2016) - Rozhdestvenskaya E. M. Elena Mikhailovna; Ermushko Zh. A. Zhanna Alexandrovna; Zhavoronok A. V. Anastasiya Valerievna; Polunina S. A. (2017, 2017)
Title screen